Occupational Performance Coaching With Parents to Promote Community Participation of Young Children With Developmental Disabilities: Protocol for a Feasibility and Pilot Randomized Control Trial - Chien, Chi-Wen; Lai, Yuen Yi Cynthia; Lin, Chung-Ying; Graham, Fiona (Frontiers in Pediatrics, 2021)
Background: High rates of restricted community participation have been reported in young children with developmental disabilities. Occupational performance coaching (OPC), grounded in self-determination theory, aims to facilitate children’s participation in life situations through coaching parents. However, there have been limited randomized controlled trials demonstrating the efficacy of OPC, especially with a specific focus on children’s community participation. The proposed study is the first step in evaluating the feasibility and acceptability of conducting a pilot randomized controlled trial of OPC in Hong Kong and testing its initial efficacy (in comparison to parent consultation) in promoting children’s community participation. Method/Design: A feasibility and pilot double-blind randomized controlled trial will be undertaken. Fifty children aged six years or below with developmental disabilities and their parents will be recruited from early intervention centers and/or through social media in Hong Kong. Parents will be randomly assigned to receive OPC or consultation, and will be blinded to group allocation. Outcomes will be assessed by blinded assessors at baseline, pre-intervention, post-intervention, and follow-up. Predetermined success criteria will be used to assess the feasibility of the trial. Qualitative interviews will be conducted with parents to explore the acceptability and perceived impact of OPC. Discussion: This trial will test whether the study protocol and OPC are feasible and acceptable, as well as assess the initial efficacy of OPC to obtain effect size estimates. The results of the trial will inform future preparations for conducting a full-scale efficacy trial of OPC. Trial Registration: ClinicalTrials.gov, U.S. National Library of Medicine, National Institutes of Health (#NCT04796909). Registered on 15th March 2021.